Coastal hazards : selected papers from EMI 2010, August 8-11, 2010, Los Angeles, California - EMI (Conference) (2010 : Los Angeles, Calif.); Huang, Wenrui, 1961-, editor; Wang, Keh-Han, editor; Chen, Qin Jim, editor; Engineering Mechanics Institute. Turbulence Committee; Engineering Mechanics Institute. Fluids Committee (Reston : American Society of Civil Engineers, 2013)
Includes bibliographical references and index